2008
DOI: 10.1002/ca.20613
|View full text |Cite
|
Sign up to set email alerts
|

A case of extensive hyperostosis frontalis interna in an 87‐year‐old female human cadaver

Abstract: Hyperostosis frontalis interna (HFI) is a condition that involves thickening of the inner surface of the frontal bone with sparing of the midline. Little is known about the etiology and clinical presentation of HFI. We report unusual findings in a woman with extensive Type D hyperostosis of the frontal bone and a large hyperostotic nodule in the parietal bone with impingement on the precentral gyrus, distinguishing this from the common form of HFI. The scalp was dissected from the cranial vault, and the calvar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…In this respect, information gained from radiographs (not otherwise available) or from direct communication with the patient's family, in addition to findings during dissection, can lead to additional opportunities for continued learning. In my own laboratory, examples of enhanced student learning that have resulted from discoveries in first patients include cadaver-based research that focuses on hyperostosis, malignant vaginal mucosal melanoma, renal cell carcinoma, dysexecutive syndrome, ineincephaly, diabetes, Lynch syndrome, Dandy-Walker malformation, intracerebral hemorrhage, and medical humanities (Talarico and Prather, 2007;Talarico et al, 2008;Talarico and Buchler, 2011;Talarico and Koveck, 2012).…”
Section: Comments From Family Members and Othersmentioning
confidence: 99%
“…In this respect, information gained from radiographs (not otherwise available) or from direct communication with the patient's family, in addition to findings during dissection, can lead to additional opportunities for continued learning. In my own laboratory, examples of enhanced student learning that have resulted from discoveries in first patients include cadaver-based research that focuses on hyperostosis, malignant vaginal mucosal melanoma, renal cell carcinoma, dysexecutive syndrome, ineincephaly, diabetes, Lynch syndrome, Dandy-Walker malformation, intracerebral hemorrhage, and medical humanities (Talarico and Prather, 2007;Talarico et al, 2008;Talarico and Buchler, 2011;Talarico and Koveck, 2012).…”
Section: Comments From Family Members and Othersmentioning
confidence: 99%
“…It was indicated by Talarico et al that area fraction of lamellar bone showed decrease in regions where extensive osseous thickening was observed in the ISFB (21). Compression of the left precentral gyrus in the location of the motor cortex was observed macroscopically.…”
Section: Location In Frontal Bone (A: Anterior Part Of the Frontal Sqmentioning
confidence: 82%
“…In histological analysis, the osseous thickening is characterized by remodelling of the ISFB into a cancellous phenotype (13,21). Microscopic analysis revealed that a larger proportion of nonwoven mature bone was present in regions of macroscopic hyperostosis.…”
Section: Location In Frontal Bone (A: Anterior Part Of the Frontal Sqmentioning
confidence: 99%
See 1 more Smart Citation
“…Como causas de hiperostosis craneal encontramos el síndrome de Klippel-Trenaunay-Weber, el sín-drome de Frölich, la enfermedad de Paget, la leontiasis ósea, el meningioma, el osteoma endosteal , los osteofitos asociados al embarazo, el síndrome de Morgagni y la displasia fibrosa 15,16 . Estas entidades deben centrar el diagnóstico diferencial con la hiperostosis frontal interna.…”
Section: Diagnóstico Diferencialunclassified